Ethnic Entrepreneurs : Identity and Development Politics in Latin America. - DeHart, Monica (Stanford University Press, 2010)
Ethnic Entrepreneurs examines how diverse groups, including Indigenous communities in Latin America and Latino communities in the United States, have become visible and valuable as agents of economic development in Latin America in recent years.